Predators do not spill over from forest fragments to maize fields in a landscape mosaic in central Argentina - Ferrante, Marco (2017)
South America is undergoing a rapid and large scale conversion of natural habitats to cultivated land. Ecosystem services (ESs) still remain important but their level and sustainability are not known. We quantified predation intensity in an Argentinian agricultural landscape containing remnants of the original chaco serrano forest by using artificial sentinel prey. We sought to identify the main predators, and the effect of landscape configuration and maize phenology on predation pressure by invertebrate and vertebrate predators in this landscape. The most common predators were chewing insects (50.4% predation events), birds (22.7%), and ants (17.5%). Overall predation rates in forest fragments (41.6% d-1) were significantly higher than in the surrounding maize fields (21.5% d-1). Invertebrate predation was higher inside and at the edge of forest fragments than within fields, and did not change with increasing distance from a fragment edge, indicating a lack of spillover from the native habitat remnants to the cultivated matrix at the local scale. Distance from a continuous forest had a positive impact on predation by invertebrates and a negative impact on vertebrate predation.